260. Quality indicators in hyperthermia treatment. (December 2018) - Di Dia, A.; Bracco, C.; Bresciani, S.; Maggio, A.; A. Miranti,; Cattari, G.; Gabriele, P.; Stasi, M
Abstract : Purpose: The development of performance indicators in the field of certification/accreditation systems and quality benchmarking is evolving. The aim of this work is to propose a set of quality indicators for hyperthermia treatments in order to provide a continuous quality improvement. Methods: A preliminary set of indicators was selected on the basis of evidenced critical issues. Three structure, six process and two outcome quality indicators were obtained. A multidisciplinary team involving different professional profiles as Radiation Oncologist, Medical Physicist and Radiation Technologists, was assembled in order to underline main critical issues in the use of hyperthermia. Results: A set of 11 indicators has been developed. For each indicator, topic, type of indicator, numerator (parameter value), denominator (reference population), standard (reference value), time period for data collection and frequency of analysis have been proposed. Numerical values for the standard were selected from the international literature, when available, and from guidelines on hyperthermia/radiotherapy, or empirically on the basis of the experience of the Italian Institutes. In the table, we reported the list of hyperthermia indicators. Conclusions: The proposed indicators are available to be investigated, in particular it will be possible to conform this type of the treatment in terms of operational procedures in order to compare different data derived from different Institutes.